The Second Skin: Ecological Role of Epibiotic Biofilms on Marine Organisms - Wahl, Martin; Goecke, Franz; Labes, Antje; Dobretsov, Sergey; Weinberger, Florian (Frontiers in Microbiology, 2012)
In the aquatic environment, biofilms on solid surfaces are omnipresent. The outer body surface of marine organisms often represents a highly active interface between host and biofilm. Since biofilms on living surfaces have the capacity to affect the fluxes of information, energy and matter across the host’s body surface, they have an important ecological potential to modulate the abiotic and biotic interactions of the host. Here we review existing evidence how marine epibiotic biofilms affect their hosts’ ecology by altering the properties of and processes across its outer surfaces. Biofilms have a huge potential to reduce its host’s access to light, gases and/or nutrients and modulate the host’s interaction with further foulers, consumers or pathogens. These effects of epibiotic biofilms may be intensely interact with environmental conditions. The quality of a biofilm’s impact on the host may vary from detrimental to beneficial according to the identity of the epibiotic partners, the type of interaction considered and prevailing environmental conditions. The review concludes with some unresolved but important questions and future perspectives.